Implementation of Good Governance through E-Governance in Modern Law Countries during the Covid-19 Pandemic - Neillisa Regga Syahputri; Eny Kusdarini (Constitutionale, 2021)
Good governance is a form of sound innovation and effective implementation of policies and reparations that are responsive to society's needs. In a modern legal state, the implementation of e-governance demands increasingly complex societal developments, especially during the Covid-19 pandemic, which can change the way people live so that all activities must coexist with technology. This article's approach is qualitative with a systematic literature review as a research method to conduct a comparative study of several kinds of literature by analyzing the data to produce accurate and valid data. This article shows the results of implementing good governance through e-governance in modern law countries by following technological developments amid the Covid-19 pandemic. One of the policies is using e-governance as a means of public service to facilitate the implementation of good governance in all areas of life.